A novel CF/Ti/β-PbO2 composite anode for zinc electrowinning: preparation, electrochemical properties and application. Issue 3 (3rd January 2023) - Hu, Changyu; Liu, Jianhua; Zhang, Man; Zeng, Siya; Guo, Shenghui; Xu, Lei; Yu, Lingfei
Abstract : The CF/Ti/β-PbO2 composite was prepared for the first time by thermal decomposition and electrodeposition. Compared with the Pb–Ag anode, the current efficiency and service life of the CF/Ti/β-PbO2 anode increased by 14.92% and 232%, respectively. Abstract : Ti and β-PbO2 coatings were successfully deposited on carbon fiber substrates by thermal decomposition and electrodeposition, and the electrochemical properties of CF/Ti/β-PbO2 composite anodes were studied in detail. The properties of titanium metal were studied via the pyrolysis of titanium hydride, and the effects of different temperatures and titanium hydride contents on carbon fiber–titanium composites as matrix materials were studied. The Ti interlayer exhibited excellent catalytic activity and electrical conductivity. The Ti interlayer plays a very important role in improving the stability of the PbO2 coating and the corrosion resistance of the CF/Ti/β-PbO2 composite anode. In comparison with the traditional lead–silver alloy anode, its electrolysis current efficiency increased by 14.92%. The corrosion rate of the CF/Ti/β-PbO2 composite anode was only 1/60 of that of the Pb–Ag anode, while its service life was 3.32 times that of the Pb–Ag anode, and 22.91 kW h per ton can be saved when electrolyzing zinc.